Teknik Akurasi Berita Oleh Humas Basarnas Bengkulu (Studi Pada Pemberitaan Evakuasi Orang Tenggelam) - Veldi Yuni Setiawan; Sri Narti; Anis Endang SM (Jurnal Multidisiplin Dehasen (MUDE), 2024)
The method used in this research uses a qualitative approach. The research subjects in this study were the Head Office of Basarnas Bengkulu, the operations sub-section and Public Relations staff of Basarnas Bengkulu. Data collection techniques using observation, interviews, and documentation. This study aims to find out the News Accuracy technique by the Public Relations of Basarnas Bengkulu. This research focuses on news accuracy by the Public Relations of Basarnas Bengkulu in obtaining information related to a case/disaster. The results showed that the News Accuracy Technique by the Public Relations of Basarnas Bengkulu can be implemented by conducting Fact Verification and Eyewitnesses as follows: 1. Fact Verification is that the fact verification process is very important in ensuring the truth and reliability of information conveyed to the public. In the context of Basarnas operations, where the delivery of precise and accurate information can have a direct impact on the safety and security of the public, verification of facts becomes the main foundation in the preparation of news. 2. Eyewitnesses i.e. in the news delivery process direct testimony from individuals who were at the scene of the incident provides valuable perspectives and details that cannot be obtained from other sources. By considering eyewitness accounts, Basarnas can supplement the information they receive and ensure the accuracy of the news delivered to the public.